Personality Traits and Performance: A Study on Hospital Nurses in Johor - Tan YH, Lucius; Salahudin, Shahrul Nizam (Research in Management of Technology and Business, 2025)
It is a complicated and variable relationship between personality traits and job performance, which has significant implications for the success of organizations and the level of satisfaction experienced by their employees. Personality traits, which are traits that serve to identify an individual's behaviour over time, play a significant role in determining how an individual approaches their work, interacts with their coworkers, and reacts to challenging situations. Thence, this study focuses on the purpose is to identifying the relationship of the five personality traits to the performance the most of hospital nurses in Johor. By using the quantitative method, 370 respondents focus on the nurses who worked in the hospital of Johor have been chosen to answer the questionnaire. Statistical Package for Social Science (SPSS) will use to analyse the data. These results may help in understanding how personality traits affect job performance allows organisations to enhance their selection and recruitment processes.